Effect of Solid-state Fermentation Parameters on Growth of Interest and Environmental Enzyme Production with Aspergillus niger - Hidalgo Zambrano, Kayna; Delgado Villafuerte, Carlos; Rosero Delgado, Ernesto (Orbital: The Electronic Journal of Chemistry, 2023)
Using residual biomass in biological processes is increasingly promoted to alleviate environmental impacts. However, the focus is mainly based on emerging technologies and limited resources, and the conditions of the technologies remain unclear. The objective of this research is to establish the conditions of a solid-state fermentation system (SSF) for the growth of fungal biomass and the production of ligninolytic enzymes of environmental interest using Aspergillus niger. In a screening step, the biomass and lipase enzyme expression of three A. niger strains obtained from different screening sites will be extended. In the second stage, the effect of packing density (ρs) and airflow (vvm) was evaluated through a 23, on the growth of fungal biomass, fiber degradation, and CO2 generation in a lipid-contaminated SSF system. The generation of biomass and the concentration of specific enzymatic activity (U/L) of lipase present a correlation for all the strains evaluated. It was estimated that the A. niger strain AN19bc isolated from sugarcane bagasse presents the highest accumulation of biomass and concentration of specific enzyme activity of lipase (0.027 U/L) after nine days. The most appropriate conditions for the production of fungal biomass of the AN19bc strain in an SSF system are presented with an airflow of 33.33 vvm and packing density ρs = 360 kg Mss/m3, levels with which Yx/s= 0.91 is reached. After the process, the solid support used in the SSF presents a change in composition, with the fiber being the component that suffers a considerable degradation of 78.70%.